Eight American Poets: An Anthology - Conarroe, Joel. (New York Random House, Inc, 1994)
The eight poets represented here, though they share certain traits and subjects, have voices that are distinctive. They all learned from others--in some cases from one another--but each one gradually transmuted those various sources into a unique style.
Keywords: Poetry